HISTORY, WORK AND EDUCATION: COMMENT ON THE INTERNAL CONTROVERSIES ON THE MARXIST FIELD - Saviani, Dermeval (2012)
The paper raises to discussion the following questions on the debate about “History, work and education” in Brazil: why the lefts, in general, and the Marxists, in particular, boast in cultivate interpretative divergences about a long range of questions whether they are theoretical or practical? What implications this phenomena have to the advance of the militants’ conscience and the revolutionary struggle? To forward the debate the problem is examined at first via the reference of the classics of Marxism to at a second moment approach the controversies surrounding the central theme of this issue of Germinal: history, work and education.